Investigating Saving and Investment Relationship: Evidence from an Autoregressive Distributed Lag Bounds Testing Approach in Liberia - Greaves, Joe Garmondyu (International Journal of Economics and Financial Issues, 2018)
The core thesis of this paper is to investigate the long-run relationships between the domestic investment and domestic savings of the Liberian economy using 1970-2016 full sample data and 1970-2012 subsample annual time series data. This paper uses the Augmented Dickey Fuller unit root test to ascertain the order of integration for the two time series variables as well as two structural breaks tests to counter check the accuracy of the unit root test. After detecting the mixed order of integration for the bivariate series, the Autoregressive Distributed Lag (ARDL) was employed using the bounds test to study the long-run linkage between the investment and saving series and the unrestricted and restricted error correction techniques within the ARDL framework to delve in the Felstein-Horioka analytical framework. The bounds test approach shows that cointegration coexist using all the samples considered in this study. Keywords: Cointegration, Saving, Investment, Felstein-Horioka, Liberia, ARDL JEL Classification: E2